Advancing Digital Transformation in Village Administration: A Study of Asset Governance via SIPADES in Krayan Bahagia Village, Paser, East Kalimantan - Risnawati, Dewi; Noor, Muhammad; Surya, Iman (Journal of Indonesian Rural and Regional Government, 2025)
This study examines the governance of village assets in Krayan Bahagia Village, Long Ikis District, Paser Regency, East Kalimantan, with a particular focus on the implementation of the Village Asset Management Information System (SIPADES) 2.0 and 3.0. Despite its significant natural resource potential, especially in the plantation sector, the village faces various structural and institutional challenges that hinder optimal asset utilization. Through a qualitative descriptive approach involving document analysis and interviews with key informants, the study identifies several core issues, including limited technical capacity among village officials, low public awareness, weak supervision mechanisms, and the suboptimal use of digital platforms such as SIPADES. The findings reveal that although regulatory frameworks support transparency and accountability, village asset governance remains constrained by human resource limitations, inadequate digital infrastructure, and sociocultural barriers such as the lack of community participation in maintenance activities. This research contributes to the discourse on rural digital transformation by analyzing the intersection of institutional capacity, administrative technology, and participatory governance. It also offers practical policy recommendations, including technical training for village officials, public education on asset stewardship, and the development of an independent supervision system. The study highlights the urgent need for integrated strategies to enhance the effectiveness of village asset governance and ensure its contribution to inclusive and sustainable rural development.